2018
DOI: 10.1016/j.antiviral.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pritelivir and acyclovir in the treatment of herpes simplex virus infections in a mouse model of herpes simplex encephalitis

Abstract: Pritelivir, a helicase-primase inhibitor, has excellent in vitro and in vivo activity against human herpes simplex virus (HSV). Mice lethally infected with HSV type 1 or 2, including acyclovir-resistant strains, were treated 72 h after infection for 7 days with pritelivir or acyclovir. Both drugs were administered orally twice daily either alone or in combination. Dosages of pritelivir from 0.3 to 30 mg/kg reduced mortality (P < 0.001) against HSV-1, E-377. With an acyclovir resistant HSV-1, 11360, pritelivir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
1
25
0
3
Order By: Relevance
“…The combination of both drugs showed an augmented, although not statistically significant, effect upon HSV-1 infection compared with the single drug treatment (Figure 4d). These results are in line with mouse data showing that a combination of pritelivir and acyclovir has an additive effect against HSV-2 infection (Quenelle et al, 2018).…”
Section: Hsv-1 Entry Receptor and Downstream Signaling Pathway In Humsupporting
confidence: 90%
“…The combination of both drugs showed an augmented, although not statistically significant, effect upon HSV-1 infection compared with the single drug treatment (Figure 4d). These results are in line with mouse data showing that a combination of pritelivir and acyclovir has an additive effect against HSV-2 infection (Quenelle et al, 2018).…”
Section: Hsv-1 Entry Receptor and Downstream Signaling Pathway In Humsupporting
confidence: 90%
“…L'AMV présente une CE 50 moyenne de 0,036 µM pour le HSV-1 et une activité 14 fois supérieure à celle du VACV [101]. Leur principal atout est de rester actif sur les virus résistants à l'ACV [102]. De plus, elles possèdent une biodisponibilité de l'ordre de 40% pour l'AMV et de plus de 60% pour le PTV, permettant donc leur administration par voie orale [103,104].…”
Section: Perspective De Nouveaux Antiviraux : Les Inhibiteurs Du Complexe Hélicase-primaseunclassified
“…The human chromosome 11 contains genes on its short arm ( Figure 2) that are found to be involved in antiviral activity. Most of the TRIM genes are localized there including TRIM 3,5,6,21,22,34,66,and 68 and are under heavy positive selective pressure. Some of these genes are also identified as viral restriction factors and TRIM 5, 22, and 34 are potent inhibitors of HIV.…”
Section: Antiviral Properties Of Trim Proteinsmentioning
confidence: 99%
“…Apart from IAV, PML, ie, TRIM19, regulates the HSV infection in complex with ND10 which is another nuclear body. Viral regulatory protein, ICPO, localize and bring about the degradation of PML, but studies conducted in BHK cells have shown that ICPO negative mutant of HSV‐1 is susceptible to the action of PML as the visible decrease in plaque formation and gene expression is observed …”
Section: Introductionmentioning
confidence: 99%